Online Reservation System / Chee Kim Shih - Chee , Kim Shih (2002)
Online Reservation System (ORS) is a system that use by travel agency to meet the need for the tourists. This system main function is provided reservation in ticket for transportation, such as bus, cruise, flight and hotel. Besides, this system also promotes the places of interest in Malaysia to tourists. This system will be separate into 2 module, which I will do the reservation in ticket for transportation and my partner will complete the module of hotel reservation. ORS allows two types of user login, the normal user (tourists) and administrator. Tourists will login as a normal user and they can make reservation for ticket and hotel. The administrator will login to manage the database and update the latest data. At the end of project, ORS will expect to have a security checking for authorized user, develop database to keep all the records, create database maintenance, feedback maintenance and creation of interactive homepages to deploy the reservation to tourists. ORS is developed using prototyping software developing model. It will be built by using Active Server Pages technologies and run on Windows 2000 Server function as Network Operating System. The Internet Information Services (IIS) 5.0 will also be using and will function as Web Server Service. For the database. the Microsoft SQL Server 7.0 will be using to create and store the relevant data. At last, I believe that this ORS will become an essential to everyone in the future and can provide lot of benefit especially to the tourists.